Bacteriology Test to Detect Coliform Bacteria in Beverages Sold at University Cafeteria in Medan - Ade Pryta Romanauli Simaremare (Buletin Farmatera, 2020)
TThe World Health Organization standard for clean and safe water is that 95% of the water samples examined do not contain coliform organisms per 100 mL. Contaminated beverages will lead to digestive tract diseases. Food poisoning cases come from contaminated can be sourced from school canteens, street vendors factories, households, family parties, and even hotels. One of the most frequent and sensitive laboratory tests to detect microorganisms contamination in water is a bacteriological examination. This research aimed to determine the microbiological quality of beverages sold in the university canteens in Medan.The microbiological examination is carried out by the Most Probable Number (MPN) method that consists of two stages, presumptive and confirmation test. From 15 samples of beverages tested, the percentage of samples contaminated with coliform bacteria was 100%, based on WHO criteria were low-risk category by 1 sample (6.7%), intermediate-risk by 5 samples (33.3%), and high-risk category by 9 samples (60%). Therefore, beverages sold in the canteen did not meet the condition for appropriateness to be consumed because of contamination by coliform bacteria.